131 treatment in dogs with hyperthyroidism caused by a non‐resectable ectopic thyroid tumour: 5 cases (2008‐2019). (4th November 2020) - Lyssens, A.; van den Berg, M. F.; Peremans, K.; Vandermeulen, E.; Daminet, S.
Abstract : Objectives: This study aimed to describe the clinical and diagnostic characteristics, as well as outcomes of radioiodine treatment in dogs with hyperthyroidism caused by a non‐resectable ectopic thyroid tumour. Materials and Methods: This retrospective study reviewed the medical records between 2008 and 2018 of dogs diagnosed with hyperthyroidism secondary to a non‐resectable ectopic thyroid tumour and treated with radioiodine. Results: Five dogs were included in the study. Three dogs had sublingual ectopic tumours, of which one also had a unilateral cervical thyroid tumour. The remaining two dogs were diagnosed with an ectopic thyroid tumour at the level of the caudal pharynx and the heart base, respectively. All cases were treated with radioiodine. The size of the ectopic masses decreased after radioiodine treatment. Total thyroxine concentrations returned to reference ranges in all dogs. Further, clinical signs of hyperthyroidism disappeared after treatment in all patients. One dog developed myelosuppression secondary to radioiodine treatment. The dog with metastasis had a very short survival compared to the four dogs without metastasis (3 months compared to 7, 36, 50 and 24 months, respectively) and succumbed most likely to thyroid‐related problems. In the remaining four dogs, their quality of life improved. They died due to diseases unrelated to the ectopic thyroid tumour. Clinical Significance: Radioiodine therapy should be considered as a treatment option in dogs diagnosed with hyperthyroidism due to a non‐resectable ectopic thyroid tumour.